2012
DOI: 10.1002/0471142301.ns1005s58
|View full text |Cite
|
Sign up to set email alerts
|

A Rubric for Extracting Idea Density from Oral Language Samples

Abstract: While past research has demonstrated that low idea density (ID) scores from natural language samples correlate with late life risk for cognitive decline and Alzheimer’s disease pathology, there are no published rubrics for collecting and analyzing language samples for idea density to verify or extend these findings into new settings. This paper outlines the history of ID research and findings, discusses issues with past rubrics, and then presents an operationalized method for the systematic measurement of ID i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 45 publications
(118 reference statements)
0
27
0
Order By: Relevance
“…We show that on the DementiaBank data the POS-based PID scores are actually higher for AD patients than they are for normal controls, contrary to the expectations from the AD literature (Engelman et al, 2010;Chand et al, 2012;Kemper et al, 2001). By studying the character-istics of the DementiaBank we are able to adapt DEPID such that its PID values become significantly different between the patient and control groups in the expected direction.…”
Section: Dependenciesmentioning
confidence: 61%
“…We show that on the DementiaBank data the POS-based PID scores are actually higher for AD patients than they are for normal controls, contrary to the expectations from the AD literature (Engelman et al, 2010;Chand et al, 2012;Kemper et al, 2001). By studying the character-istics of the DementiaBank we are able to adapt DEPID such that its PID values become significantly different between the patient and control groups in the expected direction.…”
Section: Dependenciesmentioning
confidence: 61%
“…We show that on the DementiaBank data the POS-based PID scores are actually higher for AD patients than they are for normal controls, contrary to the expectations from the AD literature (Engelman et al, 2010;Chand et al, 2012;Kemper et al, 2001). By studying the characteristics of the DementiaBank we are able to adapt DEPID such that its PID values become significantly different between the patient and control groups in the expected direction.…”
Section: Introductionmentioning
confidence: 58%
“…In order to check that we manually annotated the propositions of 20 interviews from DementiaBank according to the guidelines given by Chand et al (2012). We found that both CPIDR and DEPID overestimate the PID values although CPIDR does it to much greater extent.…”
Section: Analysis Of the Idea Densitymentioning
confidence: 99%
“…Farias et al (2012) recently reported a significant association between low PD measured in late life and steeper subsequent declines in cognitive function. Many authors describe proposition density as an index of "cognitive reserve" or a buffer against the effects of neuropathology (Chand et al, 2012;Engelman et al, 2010;Iacono et al, 2009;Snowdon et al, 1996). As mentioned earlier, PD has been shown to decline in cases of traumatic brain injury (Coelho et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown relationships between low PD scores in early adult life and greater severity of Alzheimer's disease pathology in the neocortex (Riley et al, 2005;Snowdon, Greiner, & Markesbery, 2000). Two other studies have confirmed that proposition density is not significantly different in groups with mild cognitive impairment and healthy older adults (Chand et al, 2012;Roark et al, 2011).…”
mentioning
confidence: 93%